Agroforestry Potential for Climate Change Adaptation in Buru Regency - Sinanu, Sally; Mattinahoru, Johan; Latumahina, Fransina Sarah (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Climate change poses significant challenges to tropical forest ecosystems and dependent communities, particularly through rising temperatures, altered rainfall patterns, and land-use pressures. Specific Background In eastern Indonesia, especially Buru Regency, these dynamics threaten ecosystem stability and land productivity, necessitating adaptive land management approaches such as agroforestry. Knowledge Gap However, limited empirical evidence exists regarding the biophysical characteristics and structural variability of agroforestry systems within concession-based forest management areas. Aims This study aims to analyze vegetation structure, species diversity, and development potential of climate-based agroforestry systems in the PBPH area of PT. Gema Hutani Lestari. Results The findings reveal four canopy strata (A–D) in both Wamtihut and Walsekat hamlets, indicating typical tropical forest stratification, with Wamtihut showing higher structural complexity, greater species richness (nine tree species), and moderate diversity (H’ = 1.72), while Walsekat exhibits lower diversity (H’ = 1.06) and strong dominance of Pterocymbium javanicum (IVI = 143.10). Horizontal distribution patterns include solitary, grouped, and random formations, reflecting ecological variation and land-use intensity. Notably, the absence of seedlings in both sites indicates a regeneration gap. Novelty This study provides integrated quantitative and qualitative evidence linking vegetation structure, diversity indices, and agroforestry potential within a concession-based tropical forest landscape. Implications The results highlight the need for integrated agroforestry management, institutional strengthening, and community participation to support ecosystem resilience and climate change adaptation in Buru Regency. Highlights: Multi-layer canopy composition differs markedly between two hamlets, indicating contrasting ecological conditions. One location shows moderate heterogeneity, while the other is dominated by a single pioneer species. Lack of natural regeneration signals potential long-term sustainability risks. Keywords: Agroforestry, Climate Change Adaptation, Vegetation Structure, Species Diversity, Tropical Forest